2018
DOI: 10.5603/ep.a2018.0010
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastyczny rak tarczycy z gwałtowną tyreotoksykozą — opis przypadku i przegląd literatury

Abstract: Introduction: Anaplastic thyroid carcinoma (ATC) is one of the most aggressive human malignancies and constitutes approximately 1.6-5% of the malignant neoplasms of the thyroid gland. ATC usually manifests itself with the local symptoms due to a rapidly enlarging thyroid mass, and as other thyroid cancers, has only seldom been reported to cause thyrotoxicosis. Up to now only 9 cases of ATC with concomitant thyrotoxicosis have been described. Case report: We report a rare case of a 66-year-old woman, who had ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…If we define MPT as a clinical presentation of SAT revealing infiltration of the thyroid by malignant cells, we can distinguish three categories: (a) MPT revealing a solid cancer, seventeen cases were described in the review of Jonklaas et al [5] most of which are of breast or lung cancer origin (b) MPT revealing hematological malignancies: seven cases were described in the same review, most of which are lymphomas (c) MPT revealing anaplastic carcinoma with 12 cases described in the literature including ten in the publication of Daroszewski [6] and one, published in 2020, by Fatula et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…If we define MPT as a clinical presentation of SAT revealing infiltration of the thyroid by malignant cells, we can distinguish three categories: (a) MPT revealing a solid cancer, seventeen cases were described in the review of Jonklaas et al [5] most of which are of breast or lung cancer origin (b) MPT revealing hematological malignancies: seven cases were described in the same review, most of which are lymphomas (c) MPT revealing anaplastic carcinoma with 12 cases described in the literature including ten in the publication of Daroszewski [6] and one, published in 2020, by Fatula et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported instances of primary thyroid malignancy leading to hyperthyroidism (1)(2)(3)(4)(5)(6). Thyroid metastases from non-thyroidal malignancy have also reportedly caused hyperthyroidism, most being lung, breast or hematological in origin (7).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we postulate that the mechanism of thyrotoxicosis in our patient could be follicular and stromal disruption of the thyroid parenchyma from local invasion by the OPSCC. The rapid growth of the cancer could cause necrosis of the thyroid follicles resulting in the loss of its integrity in a mechanism analogous to subacute thyroiditis (4,7,14), thereby releasing thyroxine (T4) and triiodothyronine (T3) into the circulation. This was termed "malignant pseudothyroiditis" in the context of primary thyroid carcinoma by Rosen et al (16).…”
Section: Discussionmentioning
confidence: 99%
“…Distant metastases are found in 50% of cases at the time of diagnosis ( 1 ). Case reports associated with thyrotoxicosis are rare ( 2 , 3 ).…”
Section: Introductionmentioning
confidence: 99%